جودة الحياة وعلاقتها بالحاجات الإرشادية لدى طلبة الجامعة - تيتة، وناسة (جامعة الوادي university of Eloued, 2019)
*ملخص الدراسة: تهدف الدراسة الحالية إلى الكشف عن العلاقة بين جودة الحياة والحاجات الإرشادية لدى طلبة الجامعة. ولتحقيق الهدف المرجو اعتمدت الدراسة على المنهج الوصفي بأسلوبيه الارتباطي والمقارن لأنه يناسب طبيعة هذه الدراسة, وطبقت الدراسة على عينة قوامها (189) طالبا وطالبة بجامعة الشهيد حمه لخضر في ولاية الوادي, وتم اختيارهم بالطريقة العينة العشوائية البسيطة, وقد استخدمت الدراسة مقياسين: مقياس جودة الحياة ( لصالح الشعراوي)، ومقياس الحاجات الإرشادية (حمدي عبد الله, عبد العظيم)(2013). وللتحقق من فرضيات الدراسة تم استخدام الأسلوب الإحصائي التالي بتطبيق نظام الحزمة الإحصائية للعلوم الإجتماعية: - معامل ارتباط بيرسون ‟Pearson‟للكشفعنوجودعلاقةارتباطيةدالةإحصائيابينجودةالحياةوالحاجاتالإرشادية. وقد توصلت الدراسة إلى النتائج التالية: - توجد علاقة ارتباطية ذات دلالة إحصائية بين جودة الحياة والحاجات الإرشادية لدى طلبة الجامعة. - توجد فروق ذات دلالة إحصائية في جودة الحياة بين طلبة الجامعة تبعا لمتغير الجنس. - لا توجد فروق ذات دلالة إحصائية في جودة الحياة بين طلبة الجامعة تبعا لمتغير التخصص. - لا توجد فروق ذات دلالة إحصائية في الحاجات الإرشادية بين طلبة الجامعة تبعا لمتغير التخصص. - لا توجد فروق ذات دلالة إحصائية في الحاجات الإرشادية بين طلبة الجامعة تبعا لمتغير الجنس. : The summary of the study The present study aims to discvoer the relationship between the quality of life and the guiding needs of university students for achieving the goal ,the study was based on the descriptive correlative approah And Comparative because it fits the nature of this study .this later was applied on 189 students as a sample in Hamma lakhdar university in eloued .they were selected according the random sample method .tis study used two measures :quality of life standard for ( Salah sharaui) (D.O) and the indicative needs assessment for ( Hamdiabdallah Abd eladim) (2013) .. Inorder to verify hypotheses of the study ,the following statical method was used in applying the statistical package system for social sciences:to detect there is a Statistical function relationship between quality of life correlation coefficient "Pearson" and indicative needs .. The study reached these results : - There is a correlation between Statistical significance in the quality of life and the indicative needs of university students .. - There are differences that have Statistical significance in the quality of life among university students according Sex variable .. - There are no differences that have Statistical significance in the quality of life among university students according to the variable of specialization . . - There are no differences that have Statistical significance in the extension needs among university students according to the variable of specialization.. - There are no differences that have Statistical significance in the extension needs among university students according to the sex variable .
دراسة ميدانية وصفية إرتباطية على عينة من طلبة جامعة الشهيد حمة لخضر بولاية الوادي
مذكرة ماستر في علوم التربية تخصص إرشاد وتوجيه
Keywords: الحاجات الإرشادية، جودة الحياة; Besoins de conseil, qualité de vie; Counseling needs, quality of life